Low frequency pulsed electromagnetic field promotes the recovery of neurological function after spinal cord injury in rats. Issue 2 (19th November 2018) - Li, Ziyu; Yao, Fei; Cheng, Li; Cheng, Wendan; Qi, Lei; Yu, Shuisheng; Zhang, Liqian; Zha, Xiaowei; Jing, Juehua
ABSTRACT: Low frequency pulsed electromagnetic field (LFPEMF) has been shown to provide anti‐inflammatory and antioxidative effects. However, there are no reports on whether LFPEMF can treat spinal cord injury (SCI) and its therapeutic mechanism. Therefore, this study was conducted to investigate whether LFPEMF can promote the recovery of neurological function after SCI in rats and its therapeutic mechanism. Basso‐Beattie‐Bresnahan (BBB) score and transcranial magnetic motor‐evoked potentials (tcMMEPs) were recorded to assess the recovery of neurological function. Hematoxylin and eosin (HE) staining and luxol fast blue (LFB) staining were performed to assess the severity of SCI. Immunofluorescence (IF) staining and western blotting (WB) were performed to assess the differentiation of oligodendrocyte precursor cells (OPCs) into oligodendrocytes (OLs). Toluidine blue (TB) staining was performed to assess remyelination. WB and enzyme‐linked immunosorbent assays (ELISA) were performed to assess the expression of neurotrophins and inflammatory factors. Our results showed that following stimulation by LFPEMF, there were significant improvements in BBB scores, tcMMEP amplitudes, the extent of the damage, and reduced demyelination in rats after SCI. The mature OLs, the number of well‐myelinated fibers, and the myelin sheath thickness significantly increased in rats stimulated by LFPEMF after SCI. The expression of neurotrophins significantly increased, and the expression of inflammatory factors significantly decreased in rats stimulated by LFPEMF after SCI. Therefore, we suggest that LFPEMF can promote the recovery of neurological function in rats after SCI by improving the differentiation of OPCs into OLs and promoting remyelination, as well as by inhibiting inflammation and promoting neurotrophic effects. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:449–456, 2019.